1996
DOI: 10.1111/j.1834-7819.1996.tb04855.x
|View full text |Cite
|
Sign up to set email alerts
|

The alterations of whole saliva constituents in patients with diabetes mellitus

Abstract: The present study was undertaken in order to determine the possible alterations in whole saliva and the periodontal status in patients with diabetes mellitus (DM), and was conducted on 17 patients with DM and 17 systemically and periodontally healthy subjects. When the subjects were evaluated clinically, significantly increased probing depths were noticed in the DM group when compared with the healthy subjects. In whole saliva samples, sodium, potassium, total protein, amylase, thiocyanate, and secretory IgA l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
36
1
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 23 publications
14
36
1
4
Order By: Relevance
“…Probing depth in group I (5.2 ± 0.31) was significantly higher than group II (4.28 ± 6.35) and group III (2.21 ± 0.19). These findings were consistent with the findings of Marder et al, 13 Aryeh BH 15 and Yavuzyilmaz et al 8 Our findings confirmed the general hypothesis that the degree of periodontal inflammation was more severe in the diabetic group than group II and group III.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…Probing depth in group I (5.2 ± 0.31) was significantly higher than group II (4.28 ± 6.35) and group III (2.21 ± 0.19). These findings were consistent with the findings of Marder et al, 13 Aryeh BH 15 and Yavuzyilmaz et al 8 Our findings confirmed the general hypothesis that the degree of periodontal inflammation was more severe in the diabetic group than group II and group III.…”
Section: Resultssupporting
confidence: 83%
“…This in turn increased the accumulation of plaque and calculus resulting in pronounced periodontal inflammation. Our study was in accordance with studies conducted by Sharon et al, 11 Yavuzyilmaz et al, 8 Marder et al 13 and Lindstrom et al 14 7. Probing depth in group I (5.2 ± 0.31) was significantly higher than group II (4.28 ± 6.35) and group III (2.21 ± 0.19).…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations